2015
DOI: 10.1103/physrevb.92.224510
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-induced antiferromagnetic order in Pauli-limited nodal superconductors: Application to heavy-fermionCeCoIn5

Abstract: We investigate the properties of the coexistence phase of itinerant antiferromagnetism and nodal d-wave superconductivity (Q-phase) discovered in heavy fermion CeCoIn5 under applied magnetic field. We solve the minimal model that includes d-wave superconductivity and underlying magnetic correlations in real space to elucidate the structure of the Q-phase in the presence of an externally applied magnetic field. We further focus on the role of magnetic impurities, and show that they nucleate the Q-phase at lower… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Subsequent NMR [11] and neutron scattering measurements [12,13] revealed the presence of a magnetic spin-densitywave (SDW) order in the Q phase. A number of theories were proposed for its origin [14][15][16][17][18][19][20], many of them involving additional orders, distinct from the d-wave superconductivity [21,22] and the SDW. The issue of intertwined orders (magnetic, multiple, and inhomogeneous superconductivity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent NMR [11] and neutron scattering measurements [12,13] revealed the presence of a magnetic spin-densitywave (SDW) order in the Q phase. A number of theories were proposed for its origin [14][15][16][17][18][19][20], many of them involving additional orders, distinct from the d-wave superconductivity [21,22] and the SDW. The issue of intertwined orders (magnetic, multiple, and inhomogeneous superconductivity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…De Haas-van Alphen effect measurements on Nd 1−x Ce x CoIn 5 , predictions on the behavior of the static spin susceptibility upon (non-)magnetic substitution of Ce in CeCoIn 5 and the observation of magnetic order in 5% Gd-doped CeCoIn 5 suggest that magnetic order is triggered by an instability in the band structure [41,42]. In contrast, some theoretical models argue that local magnetic droplets play a decisive role [43,44]. In this scenario magnetism is mediated inside a d-wave superconducting background via strong magnetic fluctuations triggered by the nearby SDW critical point.…”
mentioning
confidence: 99%
“…Meanwhile several theoretical proposals have been put forward to understand the origin of high field SDW phase. These theories highlight the importance of vortex lattice [11], Pauli pair breaking effect [12,13], the Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state, superconducting pairing density wave [14][15][16][17], and improved Fermi surface nesting by magnetic field [18][19][20], in stabilizing the SDW phase. Using the tight-binding parameters obtained by density functional calculations with renormalized bandwidth, it was shown that the in-plane magnetic field enhances the transverse magnetic susceptibility, χ(q, ω) in the Pauli-limited d-wave superconductors [21].…”
mentioning
confidence: 99%
“…Assuming that the 5% Nd doping has negligible effect on the Fermi surface, and the Nd atoms serve as magnetic impurities in the d-wave superconductivity, a minimal model based on a quasi-nested Fermi surface was proposed to understand arXiv:1705.07174v1 [cond-mat.supr-con] 19 May 2017 these experiments, where the magnetic impurity induces a locally SDW pattern at low field [20]. It is argued that these local SDW patterns cooperate to form a long-range SDW order, as a consequence of the Ruderman-Kittel-Kasuya-Yosida (RKKY)-like interaction between magnetic impurities.…”
mentioning
confidence: 99%
See 1 more Smart Citation